A Wideband Unidirectional Antenna Array Element With Stable Radiation Pattern - Gardill, Markus; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Antennas and Propagation in Wireless Communications, 2012)
modification of the famous Bow Tie antenna element for wideband Direction-Of-Arrival estimation antenna arrays is designed. A constant input impedance as well as a very stable radiation pattern over a 37% bandwidth from 5.5 GHz to 8 GHz is achieved. In addition the proposed design uses a double layer substrate and hence allows for direct integration of the feed network and analog RF circuitry directly into the antenna array. The particular design is suited for low-cost integration and optimized for a wireless high-precision localization system.
elib2cris::1512001600,gardill2012a